Spin-Orbit State-Selective C-I Dissociation Dynamics of the CH3I+ X̃ Electronic State Induced by Intense Few-Cycle Laser Fields - Wei, Zhengrong; Li, Jialin; See, Soo Teck; Loh, Zhi-Heng (The journal of physical chemistry letters, 2017)
Studies of ultrafast molecular dynamics induced by intense laser fields can reveal new approaches to manipulating chemical reactions in the strong-field regime. Here, we show that intense few-cycle laser pulses can induce the spin-orbit state-selective C-I dissociation of the iodomethane cation (CH3I+) in the X̃ electronic state. Irradiation of CH3I by 6 fs laser pulses with peak intensities of 1.9 × 1014 W/cm2 followed by femtosecond extreme ultraviolet probing of the iodine 4d core-level transitions reveals dissociation of the CH3I+ X̃ 2E1/2 state with a time constant of 0.76 ± 0.16 ps. By contrast, the X̃ 2E3/2 spin-orbit ground state does not exhibit any appreciable dissociation on the picosecond time scale. The observed spin-orbit state-selective dissociation of the X̃ state is rationalized in terms of the laser-induced coupling to the Ã state. Our results suggest that the intense-laser control of photodissociation channels can be potentially extended to spin-orbit split states.Studies of ultrafast molecular dynamics induced by intense laser fields can reveal new approaches to manipulating chemical reactions in the strong-field regime. Here, we show that intense few-cycle laser pulses can induce the spin-orbit state-selective C-I dissociation of the iodomethane cation (CH3I+) in the X̃ electronic state. Irradiation of CH3I by 6 fs laser pulses with peak intensities of 1.9 × 1014 W/cm2 followed by femtosecond extreme ultraviolet probing of the iodine 4d core-level transitions reveals dissociation of the CH3I+ X̃ 2E1/2 state with a time constant of 0.76 ± 0.16 ps. By contrast, the X̃ 2E3/2 spin-orbit ground state does not exhibit any appreciable dissociation on the picosecond time scale. The observed spin-orbit state-selective dissociation of the X̃ state is rationalized in terms of the laser-induced coupling to the Ã state. Our results suggest that the intense-laser control of photodissociation channels can be potentially extended to spin-orbit split states.